A taxonomic revision of Passiflora subgenus Decaloba (Passifloraceae) in Brazil - Milward-De-Azevedo, Michaele Alvim; Baumgratz, José Fernando A.; Gonçalves-Esteves, Vania (Phytotaxa, 2012)
A taxonomic revision of the Brazilian species of Passiflora subgenus Decaloba is presented. This morphological study is based on their vegetative, floral, pollen, and fruit structures. Our treatment recognizes 20 taxa divided among five supersections belonging to the subgenus in Brazil. Passiflora candollei is reported for the first time in Amazonas State, the resurrection of P. longilobis is supported, and new synonymy for P. pohlii is introduced. A key for the identification of the taxa, along with their morphological descriptions, types, examined material, common names, habitats, phenology, geographic distribution, etymology, and taxonomic comments are presented, as well as illustrations and distribution maps.